Prevalence of Cervical Intraepithelial Neoplasia among Women with Chronic Gynecological Infections: A Clinical and Hematological Study - Syeda Shaista Waheed, Hanana Hameed, Haafizah Azka Iqbal, Muhammad Tariq Hamayun Khan, Abdul Karim Soomro (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Cervical Intraepithelial Neoplasia (CIN) is a premalignant condition often associated with persistent infection and chronic inflammation of the female genital tract. Chronic gynecological infections are frequently overlooked in resource-limited settings, despite their potential to induce epithelial changes that predispose women to CIN. Hematological alterations such as anemia and inflammatory markers may reflect the systemic effects of persistent cervical inflammation, offering additional diagnostic clues. Objective: To determine the prevalence of CIN among women with chronic gynecological infections and to evaluate associated hematological changes including hemoglobin levels, ESR, CRP, and serum ferritin. Methods: This descriptive cross-sectional study was conducted from March 2022 to March 2023 at the Department of Gynecology and Obstetrics, Bolan Medical College, Quetta, and the Children Hospital and Institute of Child Health, Lahore. Ninety women aged 20 to 55 years with a history of chronic gynecological infections were enrolled. All participants underwent Pap smear screening, and those with abnormal findings were subjected to colposcopy-guided cervical biopsy for CIN confirmation. Hematological investigations were performed, and results were statistically analyzed using SPSS version 26. Results: CIN was histologically confirmed in 34 women (37.8%), with CIN I in 18.9%, CIN II in 11.1%, and CIN III in 7.8%. CIN-positive women had significantly lower hemoglobin levels (mean 10.2 g/dL), higher ESR (mean 42.1 mm/hr), and more frequent CRP positivity (70.6%) compared to CIN-negative cases (p < 0.05). Normocytic normochromic anemia was predominant among anemic participants. Serum ferritin levels were also significantly lower in CIN-positive patients, indicating chronic inflammatory consumption. Conclusion: A considerable prevalence of CIN was observed in women with chronic gynecological infections, accompanied by significant hematological alterations. The integration of cervical cytology with basic hematological screening could improve early detection of CIN, especially in resource-constrained healthcare systems. Keywords: Cervical Intraepithelial Neoplasia, Chronic Gynecological Infections, Hematology, Pap Smear, Inflammation, Anemia.